Pengaruh Metode Pembelajaran Synergetic Teaching Berbantuan Video untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPA - Teten Rohendi (Institut Pendidikan Indonesia, 2022)
This study aims to determine the effect of us video-assisted Synergetic Teaching learning methods to improve student learning outcomes in science subjects. The method used in this research is pre-experiment with one group pretest and posttest design. The population and samples used were all students of class V SDN 3 Cangkuang, Leles District, Garut Regency as many as 28 people. The data collection method used a multiple choice test of 20 questions. Data analysis used paired sample test. The results of the study show that there is an effect of using the learning method using the Synergetic Teaching method with video assistance in improving science learning outcomes. This is indicated by the results of the paired samples test with the Asymp.Sig (2-tailed) value of 0.000 < from 0.05.